Spatiotemporal Characteristics of Freezing of Gait in Patients After Hypoxic-Ischemic Brain Injury: A Pilot Study. Issue 19 (May 2016) - Yoon, Seo Yeon; Lee, Sang Chul; Kim, Yong Wook
Abstract : Abstract: The objective of this study was to investigate spatiotemporal characteristics with gait variability in patients with freezing of gait (FOG) after hypoxic-ischemic brain injury (HIBI). Eleven patients showing FOG after HIBI and 15 normal controls were consecutively enrolled. We performed gait analysis using a computerized gait system (VICON MX-T10 Motion Analysis System) and compared spatiotemporal characteristics and gait variability in both groups. Additionally, we performed correlation analysis to identify the gait parameters associated with severity of freezing, which we measured based on unified Parkinson disease Rating Scale subscore. Spatiotemporal characteristic of FOG patients showed increased stance time and double support phase and decreased swing time, single support phase, stride length, step length, and gait velocity compared with normal controls ( P < 0.05). Besides baseline spatiotemporal characteristics, step time asymmetry and step length asymmetry were significantly increased in HIBI patients with FOG ( P < 0.05). The coefficient of variation, which reflects the variability of each parameter, demonstrated increased cadence, stride time, swing time, single support phase, stride length, step length, and gait velocity variability in HIBI patients with FOG compared with normal controls ( P < 0.05). Correlation analysis between FOG severity and spatiotemporal parameters revealed gait velocity, step length, and single support phase to be spatiotemporal parameters related to FOG severity ( P < 0.05). Our findings suggest that bilateral gait coordination deterioration plays a considerable role for pathophysiology of FOG in HIBI patients. Additional studies with a larger number of subjects are needed to further investigate the neural mechanism of FOG after HIBI.